Evaluation of Handover Quality Using Fishbone Diagram Approach in Internal Disease Room of Cirebon City Hospital: Qualitative Study - Ayu, Windri Dewi; Wianti, Arni; Jaelani, Ahmad (LPPM STIKes Muhammadiyah Ciamis, 2024)
Handover in nursing refers to the systematic transfer of patient information, responsibility, and accountability from one nurse to another, which usually occurs during shift changes, but in its implementation, often experiences weaknesses that can lead to a suboptimal handover process and can disrupt the continuity of care and hinder collaborative efforts that are important in promoting patient safety. This study aims to identify the causes of the suboptimal quality of the implementation of handover between nurse shifts with the SBAR method in the internal medicine room of a hospital in Cirebon City using a qualitative method with a situation analysis approach using fishbone analysis, which has components of man, money, method, material and machine. The results of the fishbone analysis obtained five causes of the suboptimal handover process, namely nurses' knowledge of handover with SBAR is still lacking, the components in the SBAR format are not optimal in documentation, there is no definitive evaluation team, there is no monitoring instrument and the handover evaluation is not optimally monitored periodically. Therefore, the author recommends solving the problem, namely providing education or training on handover using the SBAR method for nurses, compiling instruments or checklist forms that are easier for nurses to use in handover between shifts, re-socializing the handover SOP to nurses, compiling a monitoring schedule by the head of the room or team head, forming an evaluation team and compiling a periodic evaluation schedule.